Productivity of water and heat resources and cotton yield response to cropping pattern and planting density in cotton fields in arid area - Zhenlin Dong; Sumei Wan; Yunzhen Ma; Jinbin Wang; Lu Feng; Yunlong Zhai; Tiantian Li; Zhengjun Cui; Jian Wang; Beifang Yang; Ze Yang; Zhan Zhao; et al. (Agricultural Water Management)
The individual effects of cropping patterns and planting densities on cotton yield formation and resource utilization have been extensively studied in the arid regions of western China, but research on their combined impacts remains limited. This study hypothesized that optimizing cropping patterns and planting densities would enhance hydrothermal resource productivity and cotton yield in the region. To test this, a two-year field experiment (2022–2023) employed a split-plot design with two main planting patterns (four rows per film and six rows per film) and three planting densities (low, medium, and high) as subplots. Using internet of sensor technology, soil temperature and moisture were monitored to assess their spatial and temporal distributions. The effects of planting pattern, density, and their interactions on cotton yield, yield components, biomass accumulation, and water and heat utilization were evaluated. The interaction between pattern and density significantly influenced cotton yield, harvest index, and water productivity, with planting density exerting a stronger effect on water productivity than planting pattern. In 2023, the four-row pattern at low and medium densities produced higher yields than the high-density treatment. Over the two-year period, the four-row, low-density treatment achieved 8.77 % and 13.40 % greater water productivity than the medium- and high-density treatments, respectively, while the six-row, medium-density treatment outperformed low and high densities, increasing water productivity by 3.64 % and 8.74 %. Seed cotton yield was also higher, with a 2.88 % and 6.15 % increase in the four-row, low-density treatment and an 8.51 % and 4.79 % increase in the six-row, medium-density treatment compared to higher-density treatments. The study further analyzed spatial and temporal variations in soil moisture and temperature and their link to resource productivity and cotton yield. Soil water content differences ranged from 0.10 to 0.90 mm in the four-row pattern and from 0.20 to 0.70 mm in the six-row pattern between low- and high-density treatments. Planting density significantly affected soil temperature during flowering and boll-setting stages. Lint and seed cotton yields showed positive correlations with soil heat production efficiency (PEsoil) and negative correlations with water production efficiency (WPc), with optimal patterns observed in the four-row, low-density and six-row, medium-density treatments. These findings explain why these configurations led to a higher harvest index and enhanced hydrothermal resource productivity. This study provides valuable insights into the optimal configurations for maximizing cotton yield and resource efficiency in arid regions, supporting sustainable cotton production under resource-limited conditions.